Obtaining secondary students’ perceptions of instructional quality: Two-level structure and measurement invariance - Wisniewski, Benedikt; Zierer, Klaus; Dresel, Markus; Daumiller, Martin (Learning and instruction, 2020)
Students' perceptions of instructional quality have become an important information source for teachers' professional development. This requires knowledge of the structure of these perceptions, their validity, and generalizability. To this end, we conducted a study with 15,005 German 512 grade students from 690 classrooms in three different school types and three different grade levels. Assuming three basic dimensions of instructional quality with 7 facets, we investigated the factorial structure of students' perceptions with two-level confirmatory factor analyses as well as their generalizability with two-level measurement invariance analyses. Our results confirmed the postulated factorial structure and strict invariance across subject groups, school types, and grade levels. We confirmed the same structure in teachers' assessments of their instructional quality that were positively correlated with the students' assessments. As such, these findings shed light on the structure, validity, and generalizability of students’ perceptions of instructional quality. •The structure of students' perceptions of instructional quality was investigated.•Much variation of these perceptions could be attributed to different teachers.•Distinguishing three basic dimensions with 7 facets described the data well.•A comparable factor structure was supported across: subject groups, school types, grade levels.•Students' perceptions were positively correlated with teachers' self-perceptions.